2015
DOI: 10.12693/aphyspola.128.rk.128.3.1-1
|View full text |Cite
|
Sign up to set email alerts
|

Terrylene in a 2,3-Dichloronaphthalene Crystal. New System for Optical Single-Molecule Investigations

Abstract: Results of optical studies of a new single-molecule system, terrylene molecules in a 2,3-dichloronaphthalene crystal, are presented for the rst time. Analysis of the second-order uorescence intensity correlation function shows that the external heavy-atom eect (due to the chlorine atoms) contributes to the increase of the intersystem crossing rate constant for the S1 → T1 transition, by one order of magnitude, whereas the rate constant for the T1 → S0 transition is only weakly inuenced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…3 (see DOI: 10.1039/C5FD00086F) by the black dashdot curve distribution which gives a good matching with the bulk refractive index of naphthalene. This is as well supported by the recently obtained data point for terrylene in 2,3-dichloronaphthalene as reported by M. Białkowska, et al 3 We have also added the point for terrylene in ortho-dichlorobenzene evaluated from the unsaturated spectral linewidths shown in the inset of Fig. 3 (see DOI: 10.1039/ C5FD00086F).…”
Section: Faraday Discussion Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…3 (see DOI: 10.1039/C5FD00086F) by the black dashdot curve distribution which gives a good matching with the bulk refractive index of naphthalene. This is as well supported by the recently obtained data point for terrylene in 2,3-dichloronaphthalene as reported by M. Białkowska, et al 3 We have also added the point for terrylene in ortho-dichlorobenzene evaluated from the unsaturated spectral linewidths shown in the inset of Fig. 3 (see DOI: 10.1039/ C5FD00086F).…”
Section: Faraday Discussion Discussionsupporting
confidence: 82%
“…Patrick El-Khoury commented: In RRS, where the incident photon is resonant with an excited electronic state of the material system, one oen needs to account for the various properties of that (upper) state to rationalize the observables. For RRS, Bloembergen's 48 terms [1][2][3] are reduced to 3, which retain three resonant factors in their respective denominators. One of the RRS diagrams is reminiscent of its familiar non-resonant Raman analoguewith the exception that resonant polarization is achieved (yet no excited state population is achieved).…”
mentioning
confidence: 99%
“…We rationalized such a situation in terms of the energy diagram of the electronic states of Tr, which prevents efficient spin-orbit coupling between the singlet S 1 and the triplet T 1 and T 2 states responsible for the intersystem crossing pathway. 11,20 The bright and photostable single molecules of Tr were already detected in polycrystalline 1,2-21 and 1,4-dichlorobenzenes, 22 both host matrices with heavy-atoms of chlorine.…”
Section: Optical Studies Of Single Molecules Of Tr In 23-dcn and 23mentioning
confidence: 99%
“…The preliminary results of the research were already published. 11 In the work we concentrated on deformations of the molecular structure of the guest, Tr, which were induced by the host matrix. This information could be deduced from the structure of uorescence excitation spectrum recorded at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting doped crystals ideally should preserve the desirable spectral properties of the low‐temperature fluorescent probe, such as narrow optical transitions, high spectral stability and low spectral diffusion. Recent experimental and quantum chemistry studies on terrylene in di‐substituted naphthalenes, such as 2,3‐dichloronaphthalene and 2,3‐dibromonaphthalene (DBN for short), have shown that these dihalogenated compounds can be suitable hosts for fluorescent PAH molecules ,. Here we show that the electronegativity of halogen atoms, combined with the herring‐bone crystalline structure of the host, is able to induce large electric dipoles on a centrosymmetric molecule such as dibenzoterrylene.…”
Section: Introductionmentioning
confidence: 99%